1913 Del. Laws 439, § 18 - (:unkn) unknown (General Publisher, 1913)
Prohibited children under the age of 15 from being employed, permitted or suffered to work in any establishment manufacturing, compounding, or storing nitroglycerine, dynamite, dualin, guncotton, gunpowder, or other high or dangerous explosives.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER - MINORS